Design of a nested eight‐channel sodium and four‐channel proton coil for 7T knee imaging. Issue 1 (8th August 2012) - Brown, Ryan; Madelin, Guillaume; Lattanzi, Riccardo; Chang, Gregory; Regatte, Ravinder R.; Sodickson, Daniel K.; Wiggins, Graham C.
Abstract The critical design aim for a sodium/proton coil is to maximize sodium sensitivity and transmit field homogeneity while simultaneously providing adequate proton sensitivity and homogeneity. While most dual‐frequency coils use lossy high‐impedance trap circuits or PIN diodes to allow dual‐resonance, we explored a nested‐coil design for sodium/proton knee imaging at 7 T. A stand‐alone eight‐channel sodium receive array was implemented without standard dual‐resonance circuitry to provide improved sodium signal‐to‐noise ratio. A detunable sodium birdcage was added for homogeneous sodium excitation and a four‐channel proton transmit‐receive array was added to provide anatomical reference imaging and B0 shimming capabilities. Both additional modules were implemented with minimal disturbance to the eight‐channel sodium array by managing their respective resonances and geometrical arrangement. In vivo sodium signal‐to‐noise ratio was 1.2–1.7 times greater in the developed eight‐channel array than in a mononuclear sodium birdcage coil, whereas the developed four‐channel proton array provided signal‐to‐noise ratio similar to that of a commercial mononuclear proton birdcage coil. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.